Initial Investigation of the Development A Science Practical Work Demonstration Video for SMP/MTs Oriented to Critical Thinking on the Human Excretory System - Elsi Distrima; Arief Muttaqiin (Universe, 2022)
The curriculum in Indonesia requires students to think critically. Video demonstrations on science can improve the quality of education because students learn to think critically. The purpose of this study was to determine the potential of developing a science practical work demonstration video which is oriented to critical thinking on the human excretory system. The method used in this research is the Plomp development method, which consists of three stages, namely preliminary research, prototyping stage, and assessment stage. In this article only discusses the initial investigation, namely preliminary research by provide student analysis questionnaires to 26 studenst at SMP N 1 sub-district of Guguak. The result of this initial investigation is the video demonstrations have the potential to improve students critical thinking skills.